Ambrose Bierce is Missing : And Other Historical Mysteries - Nickell, Joe (Book collections on Project MUSE., 1992)
What constitutes historical truth is often subject to change. Through ingenious detection, the accepted wisdom of one generation may become the discredited legend of another -- or vice versa. In this wide- ranging study of historical investigation, former detective Joe Nickell allows the reader to look over his shoulder as he demonstrates the use of varied techniques in solving some of the world's most perplexing mysteries.